FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PENGGUNA SISTEM INFORMASI MANAJEMEN DAERAH-KEUANGAN PEMERINTAH PROVINSI SUMATERA UTARA - Dito Aditia Darma Nasution (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2019)
This research aims to see the effect of expertise and motivation on the users performance of regional financial management information system either partially or simultaneously in the North Sumatera Provincial Government. The type of research used is associative research. The population in this research amounted to 34 regional agencies in the North Sumatera Provincial Government and the number of researchsamples was 102 people who were regional financial management information system users. The data source of this research is primary data using research instruments in the form of questionnaires. The data collection method used conducting a survey. The gathered data were analyzed by using multiple linear regression tests for analytical analysis which had been tested by using classic assumption. The results of the research showed that, partially, expertise and motivation had positive and significant influence on the users performance of regional financial management information system. Simultaneously testing showed that expertise and motivation had significant influence on the users performance of regional financial management information system.